A prelab tutoring system for Strength of Materials experiment - Chen, Chuin-Shan; Hsieh, Shang-Hsien; Chuang, Sheng-Chin; Lin, Shiu-Shin (Computer applications in engineering education, 2004)
We aim to resolve a long‐standing problem on requiring students to study how to maneuver experiments before they actually conduct them in a laboratory. A prelab tutoring system for the Strength of Materials experiment is prototyped from desired outcomes. The tutoring system utilizes a game‐like environment to engage students in learning. Consisting of highly interactive contents made by scalable vector graphics (SVGs), the system helps students to get acquainted with laboratory instruments as well as experimental procedures. The effectiveness and efficiency of the system have been confirmed through a survey among students. © 2004 Wiley Periodicals, Inc. Comput Appl Eng Educ 12: 98–105, 2004; Published online in Wiley InterScience (www.interscience.wiley.com); DOI 10.1002/cae.20004